Sintesis dan Karakterisasi Injectable Bone Substitute Berbasis Cangkang Pinctada Maxima dengan Modifikasi Konsentrasi Polyvinyl Alcohol - Susi Rahayu; Awanda Oktri P.M; M. Mukaddam Alaydrus; Ahmad Taufik S; Maz Isya A.A; Dyah Purnaning; Teguh Ardianto (Lembaga Bale Literasi, 2025)
Bone damage caused by trauma or accidents, along with the limitations of conventional treatment methods, has driven the development of more efficient bone repair strategies. Injectable Bone Substitutes (IBS) offer a minimally invasive alternative with promising clinical potential. This study aims to investigate the physical and chemical characteristics of IBS synthesized from Pinctada maxima shell-derived bioceramics, with modified concentrations of polyvinyl alcohol (PVA) as a binder component. IBS formulations were prepared by varying PVA concentrations from 0% to 12%. The resulting materials were characterized by measuring viscosity, density, injectability, and pH to evaluate their suitability as injectable bone substitutes.The addition of PVA significantly influenced the properties of the IBS. Viscosity values ranged from 0.03 to 99.77 dPa·s, with all formulations exhibiting injectability above 90%. The density values varied between 0.219 and 1.01 g/cm³, while pH values were close to neutral (around 6). The 10% PVA formulation exhibited the most favorable characteristics, with a viscosity of 25.80 dPa·s and injectability of 98.82%, suggesting optimal performance for physiological application. The modification of PVA concentration effectively tailors the physical properties of IBS materials. Further research is recommended to include setting time analysis and more in-depth pH and injectability studies to validate the material’s potential as a biocompatible injectable bone substitute.